A trade-off between cognitive and physical performance, with relative preservation of brain function. Issue 1 (December 2017) - Longman, Daniel; Stock, Jay; Wells, Jonathan
Abstract Debate surrounds the issue of how the large, metabolically expensive brains ofHomo sapiens can be energetically afforded. At the evolutionary level, decreased investment in muscularity, adiposity and the digestive tract allow for a larger brain. Developmentally, high neo-natal adiposity and preferential distribution of resources to the brain provide an energetic buffer during times of environmental stress. Through an experimental design, we investigated the hypothesis of a trade-off involving brain and muscle at the acute level in humans. Mental performance was measured by a free-recall test, and physical performance by power output on an indoor rowing ergometer. Sixty-two male student rowers performed the two tests in isolation, and then again simultaneously. Paired samplest -tests revealed that both power output and mental performance reduced when tested together compared to in isolation (t (61) = 9.699, p < 0.001 andt (61) = 8.975, p < 0.001). Furthermore, the decrease in physical performance was greater than the decrease in mental performance (t (61) = −2.069, p = 0.043). This is the first investigation to demonstrate an acute level trade-off between these two functions, and provides support for the selfish brain hypothesis due to the relative preservation of cognitive function over physical power output. The underlying mechanism is unclear, and requires further work.